2018
DOI: 10.1007/s10528-018-9844-y
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Some Circulating miRNAs in Childhood Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is a heterogeneous cancer commonly affecting children due to dysregulation of miRNA expression. In the current study, authors investigated the expression profile for miRNA-125b-1 and miRNA-203 among childhood ALL. Blood samples were collected from newly diagnosed childhood ALL and healthy control children. The expression profile for candidate miRNAs was detected using quantitative RT-PCR analysis. Statistical analysis were performed using receiver operating characteristic cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Swellam et al[ 46 ] investigated the expression signature of miRNA-125b-1 and miRNA-203 among childhood ALL, and they proposed these miRNAs as useful molecular markers for the diagnosis of childhood ALL. They noticed that the expression level of miRNA-125b-1 was significantly higher in peripheral blood (PB) isolated from 43 newly diagnosed children with ALL, while the miRNA-203 level was significantly lower in childhood ALL compared to control samples.…”
Section: Role Of Microrna In Diagnosis and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Swellam et al[ 46 ] investigated the expression signature of miRNA-125b-1 and miRNA-203 among childhood ALL, and they proposed these miRNAs as useful molecular markers for the diagnosis of childhood ALL. They noticed that the expression level of miRNA-125b-1 was significantly higher in peripheral blood (PB) isolated from 43 newly diagnosed children with ALL, while the miRNA-203 level was significantly lower in childhood ALL compared to control samples.…”
Section: Role Of Microrna In Diagnosis and Classificationmentioning
confidence: 99%
“…They noticed that the expression level of miRNA-125b-1 was significantly higher in peripheral blood (PB) isolated from 43 newly diagnosed children with ALL, while the miRNA-203 level was significantly lower in childhood ALL compared to control samples. Moreover, miRNA-125-1 was increased in T-ALL compared to other ALL phenotypes, and the miRNA-203 expression level was high in T-ALL followed by pre-B-ALL[ 46 ].…”
Section: Role Of Microrna In Diagnosis and Classificationmentioning
confidence: 99%
“…A study discovered the abnormal expression of miRNAs in blood samples of children with AL, and further indicated that miR-125b and miR-203 are potential molecular markers for diagnosing childhood AL (18). In addition, the study by Swellam et al (19) denoted that the levels of miR-143 and miR-182 in bone marrow samples of children with AL are decreased, and the prognosis of patients is poor. It reveals that abnormally expressed miRNAs play a key role in the development and progression of childhood AL.…”
Section: Discussionmentioning
confidence: 99%
“…Significant higher median levels of miR-100, miR-196a, and miR-146a were reported in blood samples of affected children compared to controls, but the diagnostic efficacy for miR-146a analysis presented superior sensitivity and specificity [ 211 ]. These same authors recently reported the significant increased expression of circulating miR-125b-1 and low levels of miR-203 in serum samples from untreated newly diagnosed children with ALL ( n = 43), as detected by quantitative RT-PCR analysis [ 212 ]. They also showed higher levels of miR-125b-1 in T-ALL samples as compared to other ALL phenotypes [ 212 ].…”
Section: Mirnas In Clinicsmentioning
confidence: 99%
“…These same authors recently reported the significant increased expression of circulating miR-125b-1 and low levels of miR-203 in serum samples from untreated newly diagnosed children with ALL ( n = 43), as detected by quantitative RT-PCR analysis [ 212 ]. They also showed higher levels of miR-125b-1 in T-ALL samples as compared to other ALL phenotypes [ 212 ]. More recently, circulating miR-652-3p was found downregulated in serum from ALL patients and levels reported as restored when patients attained in complete remission [ 47 ].…”
Section: Mirnas In Clinicsmentioning
confidence: 99%